Board Game: Sebuah Alternatif Media Pembelajaran di Masa Pandemi Covid-19 - Hana Azalia; Rizki Zakaria (Program Studi PGSD Kampus UPI di Serang, 2020)
The Covid-19 pandemic has a direct impact on the transformation of the implementation of education from face-to-face into Learning From Home (LFH). Various surveys and studies show many limitations on it, ranging from issues of zoom fatigue, socio-economics, to student interest in learning. The learning implementation guide published by the Indonesian Ministry of Education and Culture has not helped overcome problems in LFH. This descriptive qualitative research describes the use of board games in science learning for primary students. The research method used surveys and in-depth interviews with 20 students, 10 parents and 5 primary teachers. The results showed a positive response to solve the LFH problem, especially in zoom fatigue, increasing socio-economic aspects between student-parent-teachers and fostering interest in learning. Thus, board games can be an alternative media for learning science in elementary schools.